Personal Transformation and Its Influence on Visual Design Solutions - Sabyrova Aliya Sabyrkyzy (Theoretical Hypotheses and Empirical Results, 2025)
Over the past few decades, visual design has evolved significantly. The traditional view of design as a mere tool for aesthetic enhancement or functional implementation has shifted. Modern design practices now involve a deeper connection with the inner world of the creator. The process of personal transformation has become a key factor in shaping the visual decisions made by designers, influencing their creative processes and, as a result, the works they produce. This article explores the role of personal transformation in shaping visual design solutions. We will analyze how changes in a designer’s personal life, thoughts, and feelings are reflected in their work, and how this transformation can lead to innovative and more authentic design solutions.